2020
DOI: 10.1080/26395940.2020.1792807
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the distribution and risk assessment of mercury in different surficial sediments along the coastal area of the province Thai Binh in Vietnam

Abstract: Surficial sediment samples along the coastal area of the province Thai Binh in Vietnam have been collected and analysed by modified Tessier method for the mercury content. The mercury levels in these samples were found in the range between 0.12-3.79 mg/kg. Elevated concentrations were observed in some locations close to tidal marshes, large aquaculture productions or low-lying areas. The highest level of mercury was detected in a low-lying terrain near large aquaculture productions. The majority of the mercury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…At the Ba Lat estuary, at some monitoring time, Fe concentrations in the water were from 2.2 to 9.7 times higher than the allowed value QCVN 10-MT: 2015/BTNMT [12] whereas Zn concentrations were from 1.28 to 5.12 times higher than the standard limits [14]. High contents of trace metal elements (Cu, Zn, Pb, As, Cd, and Hg) in the coastal sediment of North Vietnam, including ai Binh and Nam Dinh provinces, were also observed in different studies [15,16]. is may affect the life and quality of the fishery and aquacultural seafood in this area.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…At the Ba Lat estuary, at some monitoring time, Fe concentrations in the water were from 2.2 to 9.7 times higher than the allowed value QCVN 10-MT: 2015/BTNMT [12] whereas Zn concentrations were from 1.28 to 5.12 times higher than the standard limits [14]. High contents of trace metal elements (Cu, Zn, Pb, As, Cd, and Hg) in the coastal sediment of North Vietnam, including ai Binh and Nam Dinh provinces, were also observed in different studies [15,16]. is may affect the life and quality of the fishery and aquacultural seafood in this area.…”
Section: Introductionmentioning
confidence: 79%
“…Phan [54] revealed the Cu contamination in soils of the industrial, agricultural zones, and craft villages in ai Binh Province. Some authors [13,16] reported high ranges in Hg content (from 0.12 to 3.79 mg•kg −1 , averaging 0.98 mg•kg −1 ) in the surface sediment of the Red River coastal zone, probably due to the misuse of a remarkable amount of mercurial fungicides in large aquaculture production in ai Binh Province. In addition, Nguyen et al [55] reported that high As and trace metal element contents were observed in river sediment and in the upper soil layers of the mangrove forest soil of the Red River estuary which may reflect the intensive human activities in the upstream Red River in recent decades.…”
Section: Factors Impacting On Trace Metal Element Accumulationmentioning
confidence: 99%